Options for national governments to support smallholder farmer seed systems: The cases of Kenya, Tanzania, and Uganda. - Vernooy, Ronnie (Hivos, 2017)
This brief examines how current seed policies and laws in Kenya, Tanzania, and Uganda affect smallholder farmers’ practices in terms of seed selection, saving, and storage; replanting or multiplication; sharing; improvement; and marketing. The examination is based on three measures: the degree of recognition of the roles and rights of smallholder farmers related to seed management; the degree to which policy and legal regulations facilitate smallholder-based seed management; and the level of support (moral, technical, and financial) such regulations provide for smallholder-based seed management. Together, these measures can be seen as a reflection of the degree of openness of a seed system. The current level of openness, as an approximate value, can then be compared with that of a completely open seed system. The brief concludes with some reflections about bottlenecks and opportunities for moving to more open systems. This work builds on other current research on the relation between seed policies and laws and agriculture/agricultural biodiversity/farmers’ rights/food security.